Analysis of Finger Print Bank Algorithm based Fingerprint Matching Scheme - et. al., Gousiya Begum, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Now-a-days it is an important need to preserve one’s data/information securely without giving an option to attackers or intruders to steal it. For this case authentication are considered to be the most important feature, which allows everyone to individually prove their authentication to the system and once it is correct allow them to access the features of the system otherwise neglect or block them to proceed further. There are many authentication schemes available in the information technology and security industries such as Biometric Scheme, IRIS Matching Scheme, Face Recognition, Password Management Scheme and so on. The most popular, well-known and one of the best classical scheme is called Biometric Finger Print Matching Scheme, which allows the user to register the finger print into the system for training purpose and further at every time of accessing the features into the system it gathers the present (testing) finger print from the user and match it with the already registered finger print, once it matches with the trained sample, it allows the user to login into the system or else block the user to proceed further. The proposed Finger Print Bank Algorithm uses an efficient finger print matching principles to accurately match the correct finger print and gives a Boolean result to user to inform that to proceed further or not. The Finger Print Bank Algorithm uses efficient filtering schemes to filter the finger print to extract the internal and global core details of it as well as extracts the raw code of it and compares that with the already registered finger print. For all the entire proposed approach guarantees for the best result and accuracy in results.